Systemic impacts of metabolic dysfunction-associated steatotic liver disease (MASLD) and metabolic dysfunction-associated steatohepatitis (MASH) on heart, muscle, and kidney related diseases - Sandireddy, Reddemma; Sakthivel, Suganya; Gupta, Priyanka; Behari, Jatin; Tripathi, Madhulika; Singh, Brijesh Kumar (Frontiers in Cell and Developmental Biology, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), is the most common liver disorder worldwide, with an estimated global prevalence of more than 31%. Metabolic dysfunction-associated steatohepatitis (MASH), formerly known as non-alcoholic steatohepatitis (NASH), is a progressive form of MASLD characterized by hepatic steatosis, inflammation, and fibrosis. This review aims to provide a comprehensive analysis of the extrahepatic manifestations of MASH, focusing on chronic diseases related to the cardiovascular, muscular, and renal systems. A systematic review of published studies and literature was conducted to summarize the findings related to the systemic impacts of MASLD and MASH. The review focused on the association of MASLD and MASH with metabolic comorbidities, cardiovascular mortality, sarcopenia, and chronic kidney disease. Mechanistic insights into the concept of lipotoxic inflammatory ‘spill over’ from the MASH-affected liver were also explored. MASLD and MASH are highly associated (50-80%) with other metabolic comorbidities such as impaired insulin response, type 2 diabetes, dyslipidemia, hypertriglyceridemia, and hypertension. Furthermore, more than 90% of obese patients with type 2 diabetes have MASH. Data suggest that in middle-aged individuals (especially those aged 45-54), MASLD is an independent risk factor for cardiovascular mortality, sarcopenia, and chronic kidney disease. The concept of lipotoxic inflammatory ‘spill over’ from the MASH-affected liver plays a crucial role in mediating the systemic pathological effects observed. Understanding the multifaceted impact of MASH on the heart, muscle, and kidney is crucial for early detection and risk stratification. This knowledge is also timely for implementing comprehensive disease management strategies addressing multi-organ involvement in MASH pathogenesis.